The development of a research framework for decisions to participate in the stock market: a systematic review of literatures from 2011-2021 / Koh Ho Thong and Mohd Nazri Mohd Noor - Koh, Ho Thong; Mohd Noor, Mohd Nazri (Universiti Teknologi MARA, 2021)
The purpose of this paper was to understand stock market participation among individual investors. This paper involved a descriptive systematic analysis of the empirical literature from journal indexed by Scopus, ISI and ERA with emphasis on understanding the concepts and background underlying stock market participation. Based on the review of past literature, this paper suggested that social alignment, fundamental stock literacy, and trust in institutions and stock value expectation as key concepts to understand stock market participation. The recommended framework may serve as a practical guide for stock brooking firms to understand the behavior of individual investors, encourage participation in the stock market and aid in the development of competitive marketing strategies.